Effect of Muscle Relaxant on Pain Perception among Patients of Temporomandibular Disorder - Muhammad Hassan, Shahzad Waheed Qureshi, Gulrez Amin, Muhammad Sohaib Nawaz, Tayyaba Nayab Shahid, Amna Mehwish Ikram, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of the study was to explore the impact of muscle relaxants on pain relief among patients of temporomandibular disorders. Method: This research study was based on clinical trial conducted in Oral and Maxillofacial Surgery Department of Dental Hospital, University College of Dentistry, Lahore. Data was collected from 60 patients reported the department of oral and maxillofacial surgery with complaints of myofascial pain using nonprobability convenient sampling technique. SPSS version 25. Was used for data analysis. Age and duration of symptoms were reported in mean and standard deviation whereas to calculate the effectiveness of muscle relaxant, independent sample t test was used. Results: The results of independent sample t test revealed a significant difference between the pre-treatment values and post-treatment values in terms of pain (P=.001) and mouth opening (P=.034). Pre-treatment in terms of pain, mean score was 7.70+2.4 whereas post-treatment, mean score was 4.01±1.3. Pre-treatment, in terms of mouth opening, mean score was 37.70+3.90 whereas post-treatment, in terms of mouth opening, mean score was 41.67±3.06. Conclusion: Muscles relaxant (diazepam) is quite effective in relieving TMD pain and in enhancing mouth opening due to temporomandibular disorders among patients